Analyzing EFL Learners’ Factors in Affecting English Pronunciation and The Distribution of Pronunciation Rating: A Qualitative Study - Ikrar Genidal Riadil; Rolisda Yosintha (IJELR: International Journal of Education, Language, and Religion, 2021)
Pronunciation is the production of speech sounds for communication. It is the most difficult area of English. Pronunciation teaching in English as a Foreign Language (EFL) curriculum has also been ignored for many factors. As a result, numerous EFL learners have often found it challenging to speak freely because of their weak pronunciation. This study deals with the Teaching English as a Foreign Language (TEFL) of speaking skill in EFL Learners of Indonesia. The researcher used qualitative research. There were thirty-five students who filled the questionnaire and ten students read text given First, the researcher looked for the questionnaire and found the questionnaire about Willingness to communicate. Second, the findings of tense were analyzed to know what factors that affect Indonesian learners’ English pronunciation. Third, the findings were shown into tables to know the factors. Then, the researcher asked ten learners to record when they read the text given (reading passage). After that, the researcher analyzed the pronunciation rating based on the trusted rating sheets. Finally, the researcher drew a conclusion based on the findings and discussion. This study is to investigate the factors affecting Indonesian students’ pronunciation and the distribution of pronunciation rating. The study seeks to answer two research questions (RQ): (RQ1) What are the factors affecting Indonesian learners’ English Pronunciation? and (RQ2) What are the distributions of Pronunciation Rating? This study adopted a descriptive qualitative approach which used questionnaire to build this research and reading passage. In conclusion, the researcher elaborated and answered the research questions, and explained the results and discussions about the type of factors that affect EFL learners’ in English pronunciation.